Peran Generasi Muda Penghafal Al-Quran untuk Memperkokoh Aqidah Islam di Desa Sukaraja Kecamatan Air Putih Kabupaten Batu Bara - Sucinta Dewi (Medan Resource Center, 2021)
This article seeks to study and understand how to strengthen the Islamic aqidah of the younger generation in Sukaraja village. This research was conducted in Sukaraja village, Air Putih sub-district, Batu Bara district. The younger generation is the next generation of the nation while aqidah is the foundation of religion. The method used in this study is a qualitative method by describing the facts of the field as obtained by observation, documentation, and interviews (Interview). This type of research includes field research (Field Search) and library research (library research). Field research (Field Search) is to describe and describe the situation and phenomena more clearly regarding the situation that occurred. Aqidah is the principle to build a strong, sturdy, powerful and reliable society. Aqidah is the principle of brotherhood and brotherhood. Not distinguishing between the poor and the rich, between smart and stupid, between officials and commoners, between white and black, and between Arabs and non-Arabs, except for their aqidah and piety to Allah SWT, the aqdah of the younger generation is very important because the aqdah of the younger generation will creates trust and confidence that is firmly planted in the heart as a guide and foundation for life in this world and in the hereafter.